2003
DOI: 10.1021/jp035778w
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of pH-Switchable Ion Transport and Selectivity in Nanopore Membranes with Fixed Charges

Abstract: The pH-switchable ion transport and selectivity in nanopore membranes with fixed charges is theoretically analyzed using a model based on the Nernst−Planck flux equations. The ionization state of the weak polyelectrolyte groups attached to the pore surface appears to be a crucial factor in order to understand the conductive properties of the pore. The model allows for the calculation of the fluxes of all of the ionic species involved and the membrane potential. Comparison of the theoretical results with the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 45 publications
3
55
0
Order By: Relevance
“…͑16͒ yields X Ϸ 2 / Fa for m small, that is, the volume fixed charge concentration contained in differential conical slabs of radius a. 37,38 The boundary values for the average ionic concentrations and electric potential at the pore borders r = r L and r = r R are obtained assuming that the external and pore solution average concentrations are related through the Donnan equilibrium conditions,…”
Section: ͑12͒mentioning
confidence: 99%
“…͑16͒ yields X Ϸ 2 / Fa for m small, that is, the volume fixed charge concentration contained in differential conical slabs of radius a. 37,38 The boundary values for the average ionic concentrations and electric potential at the pore borders r = r L and r = r R are obtained assuming that the external and pore solution average concentrations are related through the Donnan equilibrium conditions,…”
Section: ͑12͒mentioning
confidence: 99%
“…For the surface charge density, we have considered the values r = -0.1 and -0.5 e/nm 2 , which are equivalent to fixed charge concentrations X : -2r/FR p = 0.11 and 0.55 M. These values are typical of nanopores (Westermann-Clark and Christoforou 1986; Apel and Pretzsch 1986;Manzanares et al 1991;Ramírez et al 2003b;Chun et al 2006;Ku et al 2007). The external electrolyte concentrations have been assigned values between 0 and 0.8 M. The radii ratio R i /R p assumes values ranging from 0 (point ions) to 0.1 (R i = 0.3 nm).…”
Section: Theoretical Modelingmentioning
confidence: 99%
“…The effect of the membrane bulk nonuniformity on ion transport characteristics has been studied in a number of papers [7][8][9][10][11][12][13][14]. It was shown that the membrane transport properties, such as the electrical conductivity, diffusion, hydraulic permeability, and permselectivity, including the competition between ions with the same sign of charge, are determined by the inner membrane morphology.…”
Section: Introductionmentioning
confidence: 99%